2019
DOI: 10.1016/j.parkreldis.2019.09.029
|View full text |Cite
|
Sign up to set email alerts
|

The effect of levodopa on saccades – Oxford Quantification in Parkinsonism study

Abstract: The evaluation of novel disease modifying drugs requires biomarkers that are simultaneously sensitive to disease state but resistant to the effects of background symptomatic treatment. Saccadic eye movement parameters have been proposed as a neurophysiological biomarker for Parkinson's disease (PD) and so it is important to know how they are affected by dopaminergic medication. Studies to date are conflicting: some have concluded that medication prolongs saccadic latencies while others suggest they are shorten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 39 publications
4
37
1
Order By: Relevance
“…While some studies demonstrated increased antisaccade error rates even in unmedicated patients in very early disease stages (Antoniades et al, 2015a;Hanuška et al 2019), others found no significant alterations of antisaccade latency or antisaccade error rate early and later in the disease course. (Ranchet et al, 2017;Nagai et al, 2019) As proposed by two recent studies (Lu et al, 2019;Waldthaler et al, 2019a), antisaccade latency might correlate with disease duration in PD without significant impact of dopaminergic medication.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…While some studies demonstrated increased antisaccade error rates even in unmedicated patients in very early disease stages (Antoniades et al, 2015a;Hanuška et al 2019), others found no significant alterations of antisaccade latency or antisaccade error rate early and later in the disease course. (Ranchet et al, 2017;Nagai et al, 2019) As proposed by two recent studies (Lu et al, 2019;Waldthaler et al, 2019a), antisaccade latency might correlate with disease duration in PD without significant impact of dopaminergic medication.…”
Section: Introductionmentioning
confidence: 92%
“…CI confidence interval, HC healthy control group, PD group with Parkinson's disease, (m) mixed task design with prosaccades and antisaccades, SD standard deviation, Std. standardized ◂ (Briand et al, 1999), B14 (Bonnet et al, 2014b), B19 (Barbosa et al, 2019), C12 (Cameron et al, 2012), C00 (Crevits et al, 2000), E17 (Ewenczyk et al, 2017), G16 (Gorges et al, 2016), H10 (Harsay et al, 2010), H19 (Hanuška et al, 2019), L19 (Lu et al, 2019), L90 (Lueck et al, 1990), L16 (Lemos et al, 2016), M05 (Mosimann et al, 2005), N16 (Nemanich & Earhart, 2016), N19 (Nagai et al, 2019), R17 (Ranchet et al, 2017), RP15 (Rivaud-Péchoux et al, 2007), V19 (Visser et al, 2019), vK09 (van Koningsbruggen et al, 2009, W15 (Walton et al, 2015), W16 (Wang et al, 2016), W19 (Waldthaler et al, 2019a)…”
Section: Moderator Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Building on earlier studies that have already proposed antisaccade measures as markers for PD severity, 5,6 we provide first data indicating that antisaccade latency may be sensitive to longitudinal intraindividual improvement and deterioration of motor and cognitive symptoms in PD. Our preliminary results pave the way for future longitudinal studies with larger cohorts and longer follow-up periods.…”
mentioning
confidence: 71%
“…The SC is a critical structure in the generation of saccades, the rapid conjugate eye movements that shift gaze. Saccades have been studied extensively in PD (33-36) and more specifically in PD patients who have had DBS (37-39). The most commonly used experimental task is the visually guided prosaccade, in which the subject moves their eyes as quickly as possible towards a novel visual target.…”
Section: Discussionmentioning
confidence: 99%